Hypertriglyceridemic pancreatitis: Epidemiology, pathophysiology and clinical management. Issue 5 (1st June 2018) - de Pretis, Nicolò; Amodio, Antonio; Frulloni, Luca
Abstract : Hypertriglyceridemic pancreatitis (HTGP) typically occurs in patients with an underlying dyslipidemia (such as type I, IV or V dyslipidemia) and in the presence of a secondary condition, such as inadequately controlled diabetes, excess alcohol consumption or medication use. Although the symptoms of HTGP are similar to those of acute pancreatitis from other etiologies, HTGP is often associated with greater clinical severity and rate of complications. Therefore, accurate diagnosis of HTGP is essential so that patients receive the appropriate treatment. Novel therapies that aim to reduce the incidence of pancreatitis in this patient population are now available or in development. Understanding the etiology, pathophysiology and clinical characteristics of HTGP will enable future development of therapeutic agents to treat HTGP.